Farelo de abacaxi como fonte de fibra na alimentação de leitões desmamados - Ramos, Géssica Ferreira [UNESP] (2015)
The aim of this research was to evaluate diets with growing levels of pineapple meal, as a fiber source, in weaned piglets feeding. Fifty six piglets, from 21 to 63 days old, were fed diets composed mainly by corn, soybean meal and dairy products, with the addition of pineapple byproduct in 0%, 3,4%, 6,8% and 10,2%. The parameters evaluated were: growth performance; diarrhea incidence; diets digestibility; excretion in feces, total and per unit of weight gain, of dry (DM), mineral (MM) and organic (OM) matters, nitrogen (N) and phosphorous (P); intestinal mucosa morphology; digestive organs weight; digesta transit time; indices of costs. The trial was divided in three periods: I - from 21 to 35 days; II - from 21 to 49 days; and III - from 21 to 63 days of age. The animals were allotted into a complete randomized design, according with their weight in the beginning of the trial, with four treatments and seven repetitions. In period II the animals fed diets with 3.4 and 6.8% of pineapple meal consumed more feed (P <0.05) than those fed the control diet, and in period III only the animals that received the diet with 3.4% of pineapple presented a higher weight gain (P <0.05) than control piglets. In period III all animals fed diets with added pineapple meal presented higher (P <0.05) excretions of DM, MM, OM and N than the control animals. However, checking the excretions of these components in the feces per unit of live weight gain in period III, it was found that there was no difference (P> 0.05) among the piglets fed diets without pineapple meal and those who consumed the diet with 3.4% of the product. The use of diets with increasing levels of pineapple meal for weanling piglets worsened nutrients digestibility of diets, but no negative effect on the weights of digestive tract organs and intestinal mucosal structure were observed. There were no differences (P> 0.05) in the indices of costs evaluated. Thus, the inclusion of 3.4% of ...